Normal Threshold Size of Stimuli in Children Using a Game-Based Visual Field Test - Wang, Yanfang (Ophthalmol Ther, 2016)
INTRODUCTION: The aim of this study was to demonstrate and explore the ability of novel game-based perimetry to establish normal visual field thresholds in children. METHODS: One hundred and eighteen children (aged 8.0 ± 2.8 years old) with no history of visual field loss or significant medical history were recruited. Each child had one eye tested using a game-based visual field test ‘Caspar’s Castle’ at four retinal locations 12.7° (N = 118) from fixation. Thresholds were established repeatedly using up/down staircase algorithms with stimuli of varying diameter (luminance 20 cd/m(2), duration 200 ms, background luminance 10 cd/m(2)). Relationships between threshold and age were determined along with measures of intra- and intersubject variability. RESULTS: The Game-based visual field test was able to establish threshold estimates in the full range of children tested. Threshold size reduced with increasing age in children. Intrasubject variability and intersubject variability were inversely related to age in children. CONCLUSIONS: Normal visual field thresholds were established for specific locations in children using a novel game-based visual field test. These could be used as a foundation for developing a game-based perimetry screening test for children.